2018
DOI: 10.1159/000494300
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Therapeutic Effects of Erdosteine on Polycystic Ovary Syndrome in a Rat Model

Abstract: Objective: Polycystic ovary syndrome (PCOS) is a serious endocrine disorder. In the present study, we investigated the therapeutic effects of erdosteine in letrozole-induced PCOS in rats. Methods: Thirty-two Wistar albino female rats were grouped as control group (C), PCOS group (PCOS), PCOS-metformin group (PCOS+MET), and PCOS-erdosteine group (PCOS+Erd). PCOS was induced by administering letrozole; such rats presented with sex hormone disorder, abnormal estrous cycles determined by daily vaginal smear, large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
7
11
0
1
Order By: Relevance
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…Our further study revealed that amelioration of PCOS phenotype including hormonal disturbance may closely associated with the reduction of inflammation and the alteration of gut microbiota. In this paper, dietary inulin and metformin were demonstrated to possess capacity to alleviate PCOS throughout a series of routine indicators including pathological examination, reduced BWs, as well as rectification of abnormal hormones (T and E2), which were consistent with previous studies [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, although testosterone, DHT and letrozole are commonly employed to induce PCOS-like characteristics in pubertal or adult female rodents, it is not well understood whether androgen excess during these time periods results in organizational or activational effects. Indeed, several recent studies have assumed that letrozole treatment of pubertal female rodents causes organizational effects [47][48][49][50]. Given that our study demonstrated that letrozole treatment exerted mostly activational effects during puberty, this finding implies that letrozole treatment needs to be present for the entire duration of the study to effectively model PCOS.…”
Section: Discussionsupporting
confidence: 58%